On the Behavior of Solutions of the System of Rational Difference Equations: 𝑥𝑛+1=𝑥𝑛−1/(𝑦𝑛𝑥𝑛−1−1), 𝑦𝑛+1=𝑦𝑛−1/(𝑥𝑛𝑦𝑛−1−1), and 𝑧𝑛+1=𝑧𝑛−1/(𝑦𝑛𝑧𝑛−1−1) - Abdullah Selçuk Kurbanli (Discrete Dynamics in Nature and Society)
We investigate the solutions of the system of difference equations 𝑥𝑛+1=𝑥𝑛−1/(𝑦𝑛𝑥𝑛−1−1), 𝑦𝑛+1=𝑦𝑛−1/(𝑥𝑛𝑦𝑛−1−1), 𝑧𝑛+1=𝑧𝑛−1/(𝑦𝑛𝑧𝑛−1−1), where 𝑦0,𝑦−1,𝑥0,𝑥−1,𝑧−1,𝑧0∈ℝ.